2012
DOI: 10.1080/10934529.2012.672136
|View full text |Cite
|
Sign up to set email alerts
|

In vivoandin vitroeffect of bendiocarb on rabbit testicular structure and spermatozoa motility

Abstract: In this study the effect of bendiocarb on the rabbit testicular structure and spermatozoa motility was investigated. For testicular structure evaluation the animals were fed with bendiocarb tablets daily at a dose of 5 mg/kg of body weight for 13 days. The relative volume of the germinal epithelium, interstitium and lumen was measured. The testicular structure evaluation showed decreased relative volume of germinal epithelium in both experimental groups in comparison with the control group. The relative volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Motility was assessed at six time intervals: 0, 1, 2, 3, 4, and 5 h after spermatozoa collection and experiments were realized in six repetitions. The samples were evaluated doi: 10.17221/79/2017-CJAS using the CASA system (Computer Assisted Semen Analyser) with the Sperm Vision ® program (Minitube, Germany) equipped with a microscope Olympus BX 51 (Olympus Corp., Japan) to assess the spermatozoa motility (Massanyi et al 2008;Krockova et al 2012;Slanina et al 2015a). Each sample (10 μl) was placed into Makler Counting Chamber ® (depth 10 μm) (Sefi Medical Instruments Ltd., Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Motility was assessed at six time intervals: 0, 1, 2, 3, 4, and 5 h after spermatozoa collection and experiments were realized in six repetitions. The samples were evaluated doi: 10.17221/79/2017-CJAS using the CASA system (Computer Assisted Semen Analyser) with the Sperm Vision ® program (Minitube, Germany) equipped with a microscope Olympus BX 51 (Olympus Corp., Japan) to assess the spermatozoa motility (Massanyi et al 2008;Krockova et al 2012;Slanina et al 2015a). Each sample (10 μl) was placed into Makler Counting Chamber ® (depth 10 μm) (Sefi Medical Instruments Ltd., Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies have clearly shown that, whether determined by a computer-assisted sperm analyzer (CASA) system or simple phase-contrast microscopy, the pirethroids deltamethrin, cypermethrin and fenvalerate, as well as the organophosphates dimethoate, malathion and diazinon and the herbicides alachlor, bendiocarb, fenoxaprop-ethyl, and atrazine, can significantly reduce such parameter in humans, rodents, rabbit and boar (Table 1; Betancourt et al 2006, Grizard et al 2007, Abdallah et al 2010, Yuan et al 2010, Krockova et al 2012 followed by an increase in cell death (Betancourt et al 2006, Grizard et al 2007, Abdallah et al 2010. In parallel, the functional status of mitochondria, which is well correlated with sperm fertilizing capability (Amaral et al 2013) and widely characterized by the determination of the mitochondrial membrane potential (MMP), is also affected by EDCs (Table 1).…”
Section: Pesticidesmentioning
confidence: 99%
“…Each of the prepared samples were evaluated using a CASA system -Sperm Vision® program (Minitub, Tiefenbach, Germany) equipped with a microscope (Olympus BX 51, Japan) to assess the spermatozoa motility (Massányi et al 2008;Kročková et al 2012). Each sample was placed into Makler Counting Chamber® (depth 10 µm, Sefi-Medical Instruments, Germany).…”
Section: Motility Analysismentioning
confidence: 99%